Three different faecal egg counting techniques in ruminants - I. L. Bondarevskyi; O. V. Kruchynenko; O. O. Peredera; R. V. Peredera (Regulatory Mechanisms in Biosystems, 2024)
Diagnostics of the gastrointestinal strongiloidosises in ruminants requires methods that are characterized by high analytical sensitivity and accuracy, are easy to replicate, and quickly detect parasite eggs. At the first stage of the study, we tested the analytical sensitivity, accuracy, and precision of the method of quantitative helminthocoproscopic examination, modified McMaster technique, and Mini-FLOTAC (combined with Fill-Flotac). The faecal samples were collected from animals in Kirovohrad and Dnipropetrovsk oblasts. The known numbers of eggs isolated from bovine or sheep faeces were added to the egg-free bovine and sheep cattle stool samples to obtain the values of 10, 50, 200, and 500 eggs per gram of faeces. The objective of the study was assessment of the performances of the coprological diagnostic methods for the egg-spiked samples and samples from naturally-infested ruminants. The method of quantitative helminthocoproscopic examination proved effective in the case of a low concentration of eggs (10–50 EPG), exerting 100% analytical sensitivity. The number of eggs in 1 g of faeces detected using Mini-FLOTAC was not significantly different from the expected estimates at any level of egg density. With increase in the number of eggs to over 200 per 1 g of faeces from cows and sheep, we observed a statistical difference (Tukey’s Test) among the three methods. Using a new method of quantitative helminthocoproscopic examination, we were able to detect the highest number of naturally infested animals (54.8% of the cattle, 59.2% of the sheep, and 68.7% of the goats). Lin's concordance correlation coefficient (CCC) was the highest for sheep between the method of Quantitative Helminthocoproscopic Examination and the modified McMasters technique (CCC = 0.93). The provided data indicate the possibility of using the method we proposed in the case of low intensity of animal infestation (3-5 EPG). The prospects for future studies lie in testing the efficiency of Quantitative Helminthocoproscopic Examination on other species of animals and also in cases of their infestations with protozoa, cestodes, and trematodes.